2016
DOI: 10.1095/biolreprod.115.133637
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Arid1a in Reproductive Tract Mesenchymal Cells Reduces Fertility in Female Mice1

Abstract: Women with endometriosis can suffer from decreased fecundity or complete infertility via abnormal oocyte function or impaired placental-uterine interactions required for normal pregnancy establishment and maintenance. Although AT-rich interactive domain 1A (SWI-like) (ARID1A) is a putative tumor suppressor in human endometrial cancers and endometriosis-associated ovarian cancers, little is known about its role in normal uterine function. To study the potential function of ARID1A in the female reproductive trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 114 publications
(157 reference statements)
0
17
0
Order By: Relevance
“…ARID1A is primarily known for its roles in embryonic development (29) and as a tumor suppressor in many cancers, particularly endometriosis-related cancers of the female reproductive tract (19,22,41). However, recent findings from our group and others have established a role for ARID1A in normal uterine function and in cases of endometriosis without cancer (20, 21,41,42). In this study, we found that ARID1A plays an important role in endometrial gland development and function.…”
Section: Discussionmentioning
confidence: 49%
“…ARID1A is primarily known for its roles in embryonic development (29) and as a tumor suppressor in many cancers, particularly endometriosis-related cancers of the female reproductive tract (19,22,41). However, recent findings from our group and others have established a role for ARID1A in normal uterine function and in cases of endometriosis without cancer (20, 21,41,42). In this study, we found that ARID1A plays an important role in endometrial gland development and function.…”
Section: Discussionmentioning
confidence: 49%
“…A series of studies have determined that BAF250a plays a role in the regulation of heart and brain development (Singh & Archer, 2009; Son & Crabtree, 2014). In addition, BAF250a is required for peri‐implantation development and placenta function (Gao et al, 2008; Kim et al, 2015; Wang, Khatri, Broaddus, Wang, & Hawkins, 2016). Loss of zygotic BAF250a in homozygous mutant mice results in developmental arrest at E6.5 and absence of the mesodermal layer, indicating its critical role in early germ layer formation (Gao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, we created a mouse model harboring constitutively active TGFB receptor 1 (TGFBR1) using anti-Mullerian hormone receptor type 2 (Amhr2)-Cre recombinase (Gao et al, 2016). Amhr2-Cre has been widely used to target genes in granulosa and theca cells of the ovary, myometrial and endometrial cells of the uterus (Li et al, 2008(Li et al, , 2011Ren et al, 2009;Wang et al, 2016), and Sertoli cells and Leydig cells of the testis (Boyer et al, 2008). Expression of Amhr2-Cre has been detected as early as 11.5 days post-coitum in the urogenital ridges of both males and females, and the Cre activity is present in the somatic cells of gonads and the mesenchyme of Mullerian ducts (Jamin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%